The Forest Infanticide - a Case Study on the Removal of Brushwood from the Forests of Naoradehi Sanctuary (Madhya Pradesh) - Boaz, A. A.; Boaz, O. (Indian Forester, 1994)
The paper summarises the studies conducted in Naoradehi Sanctuary on the removal of Brushwood from the forest. An attempt has been made to quantify the magnitude of the malpractice that is being practiced as large scale infanticide under the grab of 'Nistar' facility to the farmers. This malpractice has literally wiped out the young established regeneration from our forests, so much so that it is difficult to find any saplings and poles in any forest area on the periphery of the villages. The paper suggests not only regularisation rather restriction, on this practice but also explores the possibility of educating the masses to erect live fencing of Prosopis and Thuar that are not only easy to propagate but can also serve as a means of fuelwood with high calorific value, which in turn will reduce the pressure of illicit removal of fuelwood from the forests.